Design of an Expert System for Disease Diagnosis in Chickens using the Certainty Factor Method - Sanusi; Rifky Hidayat; Ilham; Syahrul Hidayat; Sarmila Putri (Jurnal Inotera, 2025)
Chicken health is very important for the sustainability of the livestock business, considering that chicken meat is a popular and affordable commodity in Indonesia. However, many farmers still face difficulties in accurately diagnosing chicken diseases, especially with limited time and the number of experts in the field. Therefore, a system is needed that can help farmers diagnose diseases more efficiently. To overcome this problem, a web-based expert system was developed that uses the Certainty Factor method to diagnose chicken diseases. This system can be accessed online, allowing farmers to get a diagnosis and treatment advice quickly and easily, without relying on the presence of experts. With this system, it is expected to improve the accuracy of the diagnosis, reduce losses due to chicken diseases, and make it easier for farmers to maintain the health of their livestock. The results of this study indicate that the Certainty Factor method can be used well in detecting diseases in chickens. This is proven by the system's ability to predict chicken diseases according to the symptoms displayed, which have been structured based on predetermined rules